Influencia del contenido de cobalto en la estructura y absorbancia óptica de las películas de ZnO sintetizadas por rociado pirolítico - Gallozzo Cárdenas, Moisés Miguel (2018)
The ZnO is a semiconductor, which to doped with transition metals 3d is useful in applications in spintronics. Due to this motivation, we began to manufacture of thin films of 1− with x = 0, 0.05, 0.10, 0.15 and 0.20, thin films were grown by Pyrolytic Spray deposition on glass substrates (Soda Lime Glass 76 x 26 x 1 mm). Subsequently, structural and optical characterization of thin films of 1− was carried out. Structural characterization was carried out by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM), and optical characterization was performed by UV-visible spectrophotometry. In XRD a wurtzite structure characteristic of zinc was observed, where it showed a brief decrease of the peak [002] in relation to the cobalt concentration, it was also possible to see that network parameter c decreases due to doping of cobalt in structure of zinc. By SEM an increase in grain size was observed as a function of cobalt concentration and a globular formation of crystalline grains. Optical characterization confirmed that doping has occurred; Zn+2 have been replaced by Co+2 when peaks are observed at 568, 616 and 656 nm associated with interatomic transitions between Co+2 ions due to presence of a tetrahedral crystalline field in the ZnO crystal lattice